Процес розвитку міжнародного лізингу - Рижаков, Андрій Андрійович; Ryzhakov, Andriy Andriyovych (Ірпінь, 2023)
Розглянуто сутність і зміст вивчення теоретичних аспектів розвитку міжнародного лізингу, аналіз процесу розвитку міжнародного лізингу та визначення перспектив його використання на сучасному етапі. - охарактеризовано еволюцію, сутність, види, форми та принципи проведення міжнародних лізингових операцій (послуг); - досліджено механізм здійснення та законодавче регулювання міжнародних лізингових операцій; - проаналізовано міжнародний ринок лізингових послуг; - висвітлено проблеми та перспективи розвитку міжнародного лізингу.

The essence and content of the study of the theoretical aspects of the development of international leasing, the analysis of the process of the development of international leasing and the determination of the prospects for its use at the current stage are considered. - the evolution, essence, types, forms and principles of conducting international leasing operations (services) are characterized; - the mechanism of implementation and legislative regulation of international leasing operations was investigated; - the international market of leasing services was analyzed; - the problems and prospects of the development of international leasing are highlighted.
The process of development of international leasing
Keywords: лізингові угоди; лізингові компанії; міжнародний лізинг; міжнародні лізингові послуги; лізингові операції; leasing agreements; leasing companies; international leasing; international leasing services; leasing operations